Oral Delivery of miR146a Conjugated to Cerium Oxide Nanoparticles Improves an Established T Cell-Mediated Experimental Colitis in Mice - Anisha Apte; Pujarini Dutta Dey; Srisaianirudh Reddy Julakanti; Monica Midura-Kiela; Stacy M. Skopp; Jimena Canchis; Tobias Fauser; James Bardill; Sudipta Seal; David M. Jackson; Fayez K. Ghishan; Pawel R. Kiela; et al. (Pharmaceutics)
Background: Dysregulated inflammation and oxidative stress are strongly implicated in the pathogenesis of inflammatory bowel disease. We have developed a novel therapeutic that targets inflammation and oxidative stress. It is comprised of microRNA-146a (miR146a)-loaded cerium oxide nanoparticles (CNPs) (CNP-miR146a). We hypothesized that oral delivery of CNP-miR146a would reduce colonic inflammation in a mouse model of established, chronic, T cell-mediated colitis. Methods: The stability of CNP-miR146a and mucosal delivery was assessed in vitro with simulated gastrointestinal fluid and in vivo after oral gavage by quantitative real-time RT-PCR. The efficacy of orally administered CNP-miR146a was tested in mice with established colitis using the model of adoptive naïve T-cell transfer in recombinant activating gene 2 knockout (Rag2−/−) mice. Measured outcomes included histopathology; CD45+ immune cell infiltration; oxidative DNA damage (tissue 8-hydroxy-2′-deoxyguanosine; 8-OHdG); expression of IL-6 and TNF mRNA and protein, and flow cytometry analysis of lamina propria Th1 and Th17 cell populations. Results: miR146a expression remained stable in simulated gastric and intestinal conditions. miR146a expression increased in the intestines of mice six hours following oral gavage of CNP-miR146a. Oral delivery of CNP-miR146a in mice with colitis was associated with reduced inflammation and oxidative stress in the proximal and distal colons as evidenced by histopathology scoring, reduced immune cell infiltration, reduced IL-6 and TNF expression, and decreased populations of CD4+Tbet+IFNg+ Th1, CD4+RorgT+IL17+ Th17, as well as pathogenic double positive IFNg+IL17+ T cells. Conclusions: CNP-miR146a represents a novel orally available therapeutic with high potential to advance into clinical trials.